Answer:
x=-6, x=1
Step-by-step explanation:
The zero product property
It states that if a.b=0, then it must be satisfied that a=0 or b=0. It's commonly used to solve equations where one of the sides is 0.
The given equation is:
(x+2)(x+3)=12
Since neither side is 0, we operate the expression:
x^2+3x+2x+6=12
Moving 12 to the left side and simplifying:
x^2+3x+2x+6-12=0
x^2+5x-6=0
Factoring:
(x+6)(x-1)=0
Now, since there is zero on the right side, we apply the property to solve:
x+6=0, or x-1=0
The two solutions come directly:
x=-6, x=1